HUBUNGAN DUKUNGAN SUAMI DENGAN PEMILIHAN METODE KONTRASEPSI PADA WANITA USIA LEBIH DARI 35 TAHUN DAN MULTIPARITAS DI DESA KARANGLEWAS - Retnowati, Misrina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Men's concern for reproductive health has an influence on maternal health. Husband's participation in family planning programs and reproductive health is a factor that plays a role in realizing a husband who is responsible for family planning and reproductive health. This participation will be realized if various information relating to it is available in full. One reason for the low participation of husbands in family planning and reproductive health is the limited information, especially for married couples.The aim of the study was to describe husband's support and selection of contraceptive methods in women over 35 years of age and multiparity. Knowing the relationship between husband's support and the choice of contraceptive methods in women over 35 years of age and multiparity.The research method is analytical survey research with a cross sectional approach. The population is all women over the age of 35 and multiparity in the village of Kutasari with 417 people, with a sample of 81 people taken by simple random sampling. The results showed that the majority of respondents (40.74%) had good support from their husbands and most respondents (71.58%) used short-term contraceptive methods (pills, injections, condoms). There is a husband's support relationship with the selection of contraceptive methods in women over 35 years of age and multiparity with Ï value of 0.000. Conclusions there is a relationship between husband's support and the choice of contraceptive methods in women over 35 years of age and multiparity.Keywords: Husband's Support, Contraception Method Selection